2023
DOI: 10.2196/40934
|View full text |Cite
|
Sign up to set email alerts
|

Engagement With and Acceptability of Digital Media Platforms for Use in Improving Health Behaviors Among Vulnerable Families: Systematic Review

Abstract: Background The use of digital communication platforms to improve health behaviors has increased dramatically over the last decade. Public health practitioners have adopted digital communication technologies such as text messages, mobile apps, and social media to reach diverse populations. However, the effectiveness of digital communication platforms used by community-serving agencies remains unclear, and patterns of engagement and acceptability of different platforms have not been studied. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This study showed the acceptance of social media awareness campaigns as a potential channel for delivering health awareness messages. In a review that looked at engagement and acceptability of social media campaigns amongst vulnerable families (e.g., low-income parents of younger children), they found it a suitable and highly acceptable channel [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed the acceptance of social media awareness campaigns as a potential channel for delivering health awareness messages. In a review that looked at engagement and acceptability of social media campaigns amongst vulnerable families (e.g., low-income parents of younger children), they found it a suitable and highly acceptable channel [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital platforms for school meal health communication can activate behavior change, aid disease prevention, and may help students and caregivers feel more informed about heath engagement and participation. 18 As innovation in digital health continues to emerge, it is important to identify factors that may especially promote increased nutritional knowledge and health engagement, particularly as they pertain to NSLP and SBP participation. Findings from the NSLP and SBP evaluations have shown that student meal participation reduces food insecurity among children and adolescents of low-income, 19,20 and lack of proper nutrition during adolescence may have long term consequences on growth and development.…”
Section: Innovations In Technology: the Importance Of Digital Health ...mentioning
confidence: 99%
“…Digital platforms are a promising avenue to help address health inequities related to the adolescent diet and can be a user‐friendly way to provide health communication related to the school meal program. Digital platforms for school meal health communication can activate behavior change, aid disease prevention, and may help students and caregivers feel more informed about heath engagement and participation 18 . As innovation in digital health continues to emerge, it is important to identify factors that may especially promote increased nutritional knowledge and health engagement, particularly as they pertain to NSLP and SBP participation.…”
Section: Health Communicationmentioning
confidence: 99%
“…Adolescents have also benefited from digital tools, particularly in terms of improving their diet [ 26 - 28 ] and promoting sun protection habits [ 29 , 30 ]. Additionally, positive results have been observed when using apps that target multiple health risks simultaneously, both in review studies [ 31 , 32 ] and primary research [ 33 , 34 ]. However, these apps lack comprehensiveness in addressing the entirety of modifiable risk factors recognized by the ECAC.…”
Section: Introductionmentioning
confidence: 99%